Analisis Pemahaman Konsep Matematika Siswa dengan Gaya Kognitif Field Dependent pada Materi Segiempat - Asmaun Asmaun (PT. Lontara Digitech Indonesia, 2025)
Students' mathematical concept understanding of quadrilaterals needs to be explored further, especially for students with field dependent cognitive styles. The purpose of this study was to analyze students' field dependent understanding of quadrilaterals. This study was conducted in class VII MTs 1 Makassar City. The subjects in this study were 2 students with selected field dependent cognitive styles. The sampling technique used was purposive sampling by setting criteria for selecting research subjects. Data were collected through written tests and interviews. As well as data analysis techniques used qualitatively by collecting data, presenting data and drawing conclusions. The results of the study on the concept of spatial figures are: field dependent students have not succeeded in achieving the 6 specified indicators, only in spatial figures that are seen as a whole do students understand the concept of 4-sided spatial figures. In this case, students are not yet skilled enough to understand the relationship between these objects, moreover, they cannot use the principle to solve problems